Salary Bonuses in Revenue Departments : Do They Work? - De Wulf, Luc (World Bank, Washington, DC, 2012)
Compensation provides a major incentive for workers to perform well. Accordingly, bonus payments are often used to enhance staff effectiveness and efficiency-and have become increasingly common in revenue departments around the world. A recent World Bank study analyzed the bonus systems applied by revenue authorities in seven countries, and was complemented by questionnaires completed by tax and customs administrations in seven others. Though the sample was small, the study generated interesting findings and points to areas requiring further analysis. The countries analyzed indicate that bonus systems are fraught with danger and so must be designed with the utmost care. There is no evidence that bonuses automatically increase the effectiveness of revenue departments. And because staff performance is influenced by factors other than salaries and bonuses, it is not easy to determine the effects of such systems. This note reviews reasons for introducing bonus systems and discusses a number of crucial design features, particularly the importance of effective and transparent performance appraisal systems based on clear performance measures.